LARANGAN BERLEBIH-LEBIHAN DALAM AL-QUR’AN - Umi Rosyidah; Lailatul Mas’udah (JADID: Journal of Quranic Studies and Islamic Communication, 2022)
In today's era, all aspects of life have advanced and become modern. However, these good advances in science and technology are not accompanied by positive attitudes and behaviors. One of the negative attitudes that is the result of advances in science and technology is exaggeration. Exaggeration is an attitude that goes beyond reasonable limits. Several types of exaggeration occur in this modern era, including excess in eating, drinking, dressing, and using wealth. In the Qur'an, Allah has forbidden excess. But society now ignores this prohibition. even though Allah will not prohibit something if there is no mafsada or harm in it. The problems in this study are as follows: (1) How is the verse about the prohibition of excess in the Qur'an interpreted? and (2) What is the danger of excess in the Qur'an? The approach in this study uses a library research approach. By using this type of qualitative research, The method that the author uses is a method of conceptual thematic interpretation, which is a way of interpreting the Qur'an by taking a certain theme, collecting all the verses related to that theme, and seeking a complete understanding from it. In this case, the author takes the theme of the prohibition of excess in eating, drinking, dressing, and using wealth (which is material), which is explained in QS. AlA'raf (7): 31, QS. Furqan (25): 67, QS. Al-An'am (6): 141, QS. An-Nisa' (4): 6, QS. Al-Isra '(17): 26, 27, and 29.From the results of the study, it can be concluded that excess is prohibited if it exceeds the limits of needs, abilities, economics, shari'a, or even to the point of leaving obligations, and can cause mafsada for the perpetrator or those around him. As for the dangers of being extravagant, including that excess in eating and drinking can cause various diseases, excess in dressing tends to be arrogant, which is a character highly disliked by Allah. Likewise, excessive spending on assets can lead to poverty. Moderation and middle-of-the-road attitudes (neither excessive nor stingy) are Islamic guidelines in matters of wealth, society, and religion. Because avoiding excess and adopting a simple life can increase faith and make it easier to face all the tests given by Allah. Keywords: Al-Qur?an, Larangan, Berlebih-lebihan.